THE EFFECT OF ADDITION OF BUFFER GASES ON THE OUTPUT ENERGY AND PULSE WIDTH OF AMMONIA LASER - Hamza, F.; Wasfi, A.; Ali, F. (Iraqi Journal of Science, 2024)
We present the design of a pulsed ammonia laser, which is optically pumped by a TEA CO2 laser. The effect of addition of buffer gases to the ammonia gas laser (such as N2, He and Ar with different mixing ratios) on the output energy and pulse width of the laser was studied. It was found that N2 gas was preferable among the other additives as it provides highest output pulse energy and increasing the laser efficiency. The addition of N2 gas helped also in obtaining more than 40 ammonia laser lines around the 12μm, which was step tunable in the spectral range of (762-968 cm-1).